Home-Based Versus Outpatient-Based Cardiac Rehabilitation Post–Coronary Artery Bypass Graft Surgery: A Randomized Controlled Trial. Issue 3 (May 2022) - Takroni, Mohammed A.; Thow, Morag; Ellis, Brian; Seenan, Christopher
Abstract : Background: The prevalence of coronary heart disease continues to increase in the Kingdom of Saudi Arabia (KSA). Despite advances in cardiac surgery, there are no established outpatient cardiac rehabilitation programs in the KSA. Objective: The aim of this study was to investigate the effectiveness of home-based cardiac rehabilitation compared with outpatient-based cardiac rehabilitation and usual care for patients who are post–coronary artery bypass graft surgery. Method: This 3-arm, single-blind, randomized controlled trial was carried out at the King Faisal Specialist Hospital, Riyadh, KSA. A total of 82 patients post–coronary artery bypass graft surgery were randomized and 73 patients completed the study. Recruited patients were distributed to home-based cardiac rehabilitation (n = 24), outpatient-based cardiac rehabilitation (n = 25), or usual care (control group) (n = 24). Participants in the intervention groups completed an individualized exercise program for 2 hours, 3 times a week for 8 weeks. The control group followed usual care (no intervention). The incremental shuttle walk test (ISWT), metabolic equivalence task, Short Form-36, and Hospital Anxiety and Depression Scale (HADS) were measured at baseline, postintervention, and after a 4-week follow-up period. Results: Postintervention, there was an increase in mean ISWT score from baseline in both the home-based cardiac rehabilitation and outpatient-based cardiac rehabilitation groups (66 [0.58] m and 71 [9.19] m, respectively). No difference was observed in the control group. At the 4-week follow-up, both intervention groups showed statistically significant improvements in all outcome measures (ISWT, metabolic equivalence tasks, HADS-A, HADS-D, and Short Form-36) compared with baseline (all P < .001). The home-based cardiac rehabilitation group showed statistically continuous improvement compared with the outpatient-based cardiac rehabilitation group. The control group did not show any significant changes across time in outcome measures. Conclusion: Home-based cardiac rehabilitation is as effective as outpatient-based cardiac rehabilitation. Home-based cardiac rehabilitation appears to be more effective at maintaining improvements follow the end of the intervention.